Preparation method of graphene-copper-silicon composite material and lithium battery negative electrode prepared from graphene-copper-silicon composite material

Through the preparation method of graphene-copper-silicon composite, the problem of reduced capacity and poor rate performance caused by volume expansion and low conductivity of the lithium battery negative electrode material during charging and discharging is solved, and a lithium battery negative electrode material with high specific capacity and good rate performance is achieved.

CN119725411APending Publication Date: 2025-03-28QINGHAI HUANGHE HYDROPOWER DEVELOPMENT CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311258168.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the charging and discharging process, the existing lithium battery negative electrode materials have reduced capacity and poor rate performance due to the volume expansion and low conductivity of the silicon material, and the preparation process is complicated and the morphology is poor.

Method used

The graphene-copper-silicon composite material preparation method is adopted, and the composite structure of graphene-copper-silicon composite is formed by grinding and mixing silicon powder, copper powder and polymethyl methyl acrylate particles, heat treatment and acid solution corrosion.

Benefits of technology

In-situ coating of silicon nanoparticles is achieved, volume expansion is suppressed, conductivity is enhanced, rate performance and specific capacity is improved, and the process is relatively simple and the morphology is controlled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725411A_ABST
    Figure CN119725411A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a graphene-copper-silicon composite material and a lithium battery negative electrode prepared from the graphene-copper-silicon composite material, and belongs to the technical field of lithium battery negative electrode materials. The preparation method of the graphene-copper-silicon composite material comprises the following steps: grinding and uniformly mixing silicon powder, copper powder and polymethyl methacrylate particles to obtain black powder; the black powder is dried, then the dried black powder is placed in inert protective gas to be subjected to heat treatment, and red powder is obtained; the red powder is placed in an acid solution to be stirred and corroded, then vacuum filtration and drying are conducted, yellow white powder is obtained, and the obtained yellow white powder is the graphene-copper-silicon composite material. Graphene in the graphene-copper-silicon composite material wraps copper nano-particles and silicon nano-particles, a graphene shell plays a role in inhibiting volume expansion of the silicon nano-particles in the lithium de-intercalation process, in addition, the copper nano-particles and the graphene shell jointly form a conductive network, and the overall conductivity of the graphene-copper-silicon composite material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials for lithium batteries, and in particular relates to a method for preparing a graphene-copper-silicon composite material and a negative electrode for a lithium battery. Background Art

[0002] Silicon materials are considered to be the most promising negative electrode materials due to their suitable discharge potential and abundant reserves. However, their volume expansion of up to 300% during lithium ion insertion / extraction can cause the electrode to shatter. In addition, they face the uncontrollable growth of the solid electrolyte interface (SEI) during charge and discharge, which leads to a rapid decrease in the capacity and coulombic efficiency of lithium-ion batteries. At the same time, silicon electrodes also face the problems of low intrinsic conductivity and ultra-low lithium ion diffusion coefficient (10 -14 -10 -13 cm -2 ·s -1 ), which results in a large internal resistance of the silicon electrode, low energy utilization, slowed charge transfer and attenuated rate performance.

[0003] Currently, graphite materials are commonly used in commercial lithium battery negative electrodes, but they have the disadvantages of low theoretical specific capacity (372mAh / g) and low lithium deintercalation potential. Subsequently, silicon-containing negative electrodes were gradually used in 3C products and power batteries due to their higher theoretical specific capacity (3578mAh / g). However, in existing negative electrode materials, the silicon source is simply embedded between graphite sheets. During long-term charging and discharging, there are three main problems: 1) As the spacing between graphite sheets increases, the silicon source gradually falls off; 2) The volume expansion of the silicon source is as high as 300%, and as the lithium ions are embedded, it gradually expands and breaks and fails; 3) Due to the low conductivity of silicon, the cycle performance of silicon negative electrodes at high rates is poor. Therefore, developing a silicon-lithium battery negative electrode material with high capacity and suppressible volume expansion of the silicon source is currently a research hotspot in the field of silicon-lithium battery negative electrode material technology. For example, patent CN20211044589 discloses a nano-silicon / sub-silicon composite material for lithium battery negative electrode, the preparation process of the material is complex, and the morphology controllability is poor; CN110943203 discloses a silicon-graphite composite material, but the silicon particles are simply embedded in the graphite layer, and the structure cannot effectively inhibit the silicon particles from falling off; CN101924211A discloses a method for preparing a negative electrode material for a graphene / silicon lithium-ion battery, which combines graphene and silicon powder by a simple physical mixing method, resulting in a decrease in the proportion of silicon in the material, and the specific capacity as a negative electrode is also reduced. CN110048098A discloses a method for preparing a nitrogen-doped graphene-coated nano-silicon composite material. Although the material has a good charge and discharge capacity, the surfactant added in its preparation process cannot be completely removed, and it may cause safety risks in practical applications as a negative electrode for lithium batteries. Summary of the invention

[0004] In view of the above problems, the present invention provides a method for preparing a graphene-copper-silicon composite material and a lithium battery negative electrode thereof.

[0005] The first object of the present invention is achieved by the following technical solutions:

[0006] A method for preparing a graphene-copper-silicon composite material, comprising:

[0007] Grind and mix silicon powder, copper powder and polymethyl methacrylate particles to obtain black powder;

[0008] The black powder is dried, and then the dried black powder is heat-treated in an inert protective gas to obtain a red powder;

[0009] The red powder is placed in an acid solution and stirred for corrosion, followed by vacuum filtration and drying to obtain a yellow-white powder, which is a graphene-copper-silicon composite material.

[0010] Furthermore, the mass ratio of the silicon powder, copper powder and polymethyl methacrylate particles is 0.1-0.2:1-2:1-1.5.

[0011] Furthermore, the grinding time is greater than 30 minutes.

[0012] Furthermore, the drying temperature is 80-100°C.

[0013] Furthermore, the heat treatment temperature is 550-650° C., and the heat treatment time is 1-2 hours.

[0014] Furthermore, the acid solution is a 1.8-2.2 mol / L nitric acid or hydrochloric acid solution, the stirring speed is 200-300 r / min, and the stirring corrosion time is 1-2 h.

[0015] Furthermore, the drying temperature is 40-50°C.

[0016] The second object of the present invention is achieved by the following technical solutions:

[0017] A graphene-copper-silicon composite material is prepared by the above method and comprises graphene, copper nanoparticles and silicon nanoparticles, wherein the graphene wraps the copper nanoparticles and the silicon nanoparticles.

[0018] The third object of the present invention is achieved through the following technical solutions:

[0019] A graphene-copper-silicon composite material for a lithium battery negative electrode material, wherein the graphene-copper-silicon composite material is prepared by the above method;

[0020] After the graphene-copper-silicon composite material is mixed with a binder, a lithium battery negative electrode material of the graphene-copper-silicon composite material is obtained.

[0021] Furthermore, the binder is one of phenolic resin, urea-formaldehyde resin, asphalt, PVP, cellulose acetate, sodium carboxymethyl cellulose, and polyacrylonitrile, and the mass ratio of the binder to the graphene-copper-silicon composite material is 1:8-10.

[0022] Beneficial effects of the present invention:

[0023] The graphene-copper-silicon composite material prepared by the present invention is formed by catalytic degradation of PMMA by copper nanoparticles in a hydrogen environment through nano-silicon powder, nano-copper powder and polymethyl methacrylate powder to form a graphene-copper block-silicon composite, which is further subjected to corrosion adjustment to form a graphene-copper-silicon composite material. The graphene wraps the copper nanoparticles and the silicon nanoparticles, and the copper nanoparticles are dispersed between the graphene shell and the silicon particles, so that the silicon nanoparticles are coated by the in-situ graphene-copper conductive network. The graphene shell functions to inhibit the volume expansion of the silicon nanoparticles during lithium insertion and extraction. In addition, the copper nanoparticles and the graphene shell jointly form a conductive network to enhance the overall conductivity of the graphene-copper-silicon composite material. In summary, the graphene-copper-silicon composite material has the advantages of regular morphology, small volume expansion effect, excellent conductivity, good rate performance, etc.

[0024] The graphene-copper-silicon composite negative electrode lithium battery made of the graphene-copper-silicon composite material has high specific capacity and high rate performance.

[0025] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 A flow chart of a method for preparing a graphene-copper-silicon composite material according to an embodiment of the present invention is shown;

[0028] Figure 2 The SEM image of the graphene-copper-silicon composite material in Example 1 of the present invention is shown;

[0029] Figure 3 The TEM image of the graphene-copper-silicon composite material in Example 1 of the present invention is shown;

[0030] Figure 4 The figure shows a rate curve of a negative electrode of a lithium battery made of a graphene-copper-silicon composite material in Example 2 of the present invention;

[0031] Figure 5 The TEM image of the carbon-silicon composite material in Comparative Example 1 of the present invention is shown;

[0032] Figure 6 The rate curve of the negative electrode of a lithium battery made of the carbon-silicon composite material in Comparative Example 2 of the present invention is shown;

[0033] Figure 7 The TEM image of the copper-silicon composite material in Comparative Example 3 according to the present invention is shown;

[0034] Figure 8 The figure shows the rate curve of the negative electrode of a lithium battery made of the copper-silicon composite material in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] like Figure 1 As shown, a method for preparing a graphene-copper-silicon composite material according to an embodiment of the present invention includes:

[0037] Step 1: Grind and mix silicon powder, copper powder and polymethyl methacrylate particles to obtain black powder;

[0038] Step 2, drying the black powder, and then heat-treating the dried black powder in an inert protective gas to obtain a red powder;

[0039] Step 3: placing the red powder in an acid solution for stirring and corrosion, followed by vacuum filtration and drying to obtain a yellow-white powder, which is a graphene-copper-silicon composite material.

[0040] In the embodiment of the present invention, the mass ratio of the silicon powder, copper powder and polymethyl methacrylate particles is 0.1-0.2:1-2:1-1.5;

[0041] Most preferably, the mass ratio of the silicon powder, copper powder, and polymethyl methacrylate particles is 0.1:1:1 or 0.1:2:1;

[0042] The mass ratio of the silicon powder, copper powder and polymethyl methacrylate particles may also be one of 0.2:1:1, 0.1:1.2:1.5, 0.1:2:1.2, 0.2:1:1 and 0.1:2:1.5.

[0043] In the embodiment of the present invention, the particle size of the silicon powder is 50-150 nm, and the particle size of the copper powder is 400-600 nm;

[0044] Preferably, the particle size of the silicon powder is 100 nm, and the particle size of the copper powder is 500 nm;

[0045] The particle size of the silicon powder can also be any one of 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, and 150nm, and the particle size of the copper powder can also be any one of 400nm, 420nm, 4500nm, 520nm, 530nm, 540nm, 550nm, 560nm, 570nm, 580nm, 590nm, and 600nm.

[0046] In an embodiment of the present invention, the grinding time is greater than 30 minutes.

[0047] In the embodiment of the present invention, the drying temperature is 80-100°C.

[0048] In an embodiment of the present invention, the heat treatment process is carried out in a tube furnace, the inert gas is high-purity (99.99%) argon or high-purity (99.99%) nitrogen, the purge flow rate is 100-200 mL / min, the heat treatment temperature is 550-650°C, the heat treatment time is 1-2h, and the heating rate of the tube furnace is 10-15°C / min;

[0049] Most preferably, the purge flow rate of the inert gas is 200 mL / min, the heat treatment temperature is 600° C., the heat treatment time is 1 h, and the heating rate of the tube furnace is 10° C. / min;

[0050] The purge flow rate of the inert gas can also be one of 100 mL / min, 110 mL / min, 120 mL / min, 130 mL / min, 140 mL / min, 150 mL / min, 160 mL / min, 170 mL / min, 180 mL / min, and 190 mL / min.

[0051] The heat treatment temperature may also be one of 550°C, 560°C, 570°C, 580°C, 590°C, 610°C, 620°C, 630°C, 640°C, and 650°C.

[0052] In the embodiment of the present invention, the acid solution is a 1.8-2.2 mol / L nitric acid or hydrochloric acid solution, the stirring speed is 200-300 r / min, and the stirring corrosion time is 1-2 h;

[0053] Most preferably, the acid solution is 1.8 mol / L nitric acid;

[0054] The acid solution may also be one of 1.9 mol / L nitric acid, 2.0 mol / L nitric acid, 2.1 mol / L nitric acid, 2.2 mol / L nitric acid, 1.8 mol / L hydrochloric acid, 1.9 mol / L hydrochloric acid, 2.0 mol / L hydrochloric acid, 2.1 mol / L hydrochloric acid, and 2.2 mol / L hydrochloric acid.

[0055] In the embodiment of the present invention, the drying temperature is 40-50°C.

[0056] Example 1

[0057] Preparation of an in-situ coated graphene-copper-silicon composite material:

[0058] Step 1: Weigh 0.2 g of silicon particle powder with an average particle size of 100 nm, 1 g of copper nanoparticle powder with a particle size of 500 nm, and 1 g of PMMA powder, grind them in an agate mortar for more than 30 minutes, and mix them evenly to obtain a black powder;

[0059] Step 2: Dry the black powder in a vacuum oven at 80°C for 1 hour to remove excess moisture; then place the dried black powder in a pure argon protective gas with a purity of 99.9% at a gas flow rate of 100 ml / min, and heat it at a rate of 10°C / min, keep it at 600°C for 1 hour, and then cool it naturally to obtain a red powder, thereby obtaining a graphene-copper block-silicon composite material;

[0060] Step 3: Take 1 g of graphene-copper block-silicon composite material, place it in 100 ml of dilute nitric acid solution (1.8 mol / L), stir it magnetically at 200 rpm for 30 min, and then obtain the in-situ coated graphene-copper-silicon composite material (i.e., graphene-copper-silicon composite material) by vacuum filtration.

[0061] The graphene-copper-silicon composite material obtained in this example was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the results obtained are as follows: Figure 2 and Figure 3 As shown, the SEM image is as follows Figure 2As shown in the TEM image Figure 3 As shown;

[0062] from Figure 2 and Figure 3 It can be seen that the graphene-copper-silicon composite material forms a coating structure, and the coating structure is complete, and the particles in the coating are evenly dispersed and not agglomerated, indicating that in this example, the organic precursor PMMA completely forms graphene under the catalysis of copper particles ( Figure 3 In the figure, the wrinkled structure under the particles is graphene, the coating structure is complete, the copper nanoparticles are evenly dispersed without agglomeration, and the silicon nanoparticles are evenly dispersed without adhesion.

[0063] Example 2

[0064] The in-situ coated graphene-copper-silicon composite material prepared in Example 1 was mixed with a sodium carboxymethyl cellulose binder at a mass ratio of 8:1 to obtain a negative electrode for a lithium battery.

[0065] The upper electrode material was subjected to electrochemical rate performance tests at different current densities, and the rate curves were obtained as shown in the figure. Figure 4 As shown;

[0066] Figure 4 In the figure, the axial coordinate Capacity is the capacity, and the horizontal coordinate Cycle number is the number of cycles;

[0067] from Figure 4 It can be seen that in the capacity test of the lithium battery negative electrode in this embodiment at different current densities, the initial capacity is as high as 2000mAh / g, the attenuation amplitude is small under high current density cycling and can recover to more than 90% of the initial capacity under low current density, indicating that the structure is stable and the cycle performance is good;

[0068] The electrochemical rate performance tests under the above-mentioned different current densities show that the in-situ coated graphene-copper-silicon composite material lithium battery negative electrode prepared in Example 1 has a high specific capacity under the conductive support of the coating structure and copper particles, and can still recover to a high specific capacity after rate cycling, indicating that the structure has strong stability and good cycle performance.

[0069] Comparative Example 1

[0070] A method for preparing a carbon-silicon composite comprises the following steps:

[0071] S100: Weigh 0.2 g of silicon particle powder with an average particle size of 100 nm and 1 g of PMMA powder, grind them in an agate mortar for more than 30 min, and mix them evenly to obtain an earthy white powder;

[0072] S200: Dry the powder in a vacuum oven at 80°C for 1 hour to remove excess moisture; place the dried powder in a pure argon protective gas with a purity of 99.9% at a gas flow rate of 100 mL / min, and heat it at a rate of 10°C / min. Keep it at 600°C for 1 hour and then cool it naturally to obtain a black powder, thereby obtaining a carbon-silicon composite material.

[0073] The carbon-silicon composite material obtained above was observed by transmission electron microscopy (TEM), and the results were as follows: Figure 5 As shown;

[0074] from Figure 5 It can be seen that there is a coating structure, but the coating structure is incomplete and the silicon nanoparticles are seriously agglomerated, which shows that carbon coating is formed on the surface of silicon nanoparticles, but without the catalytic effect of copper nanoparticles, the organic precursor cannot form graphene ( Figure 5 There is no wrinkled structure in the composite), and the lack of copper particles causes serious agglomeration of silicon nanoparticles in the composite.

[0075] Comparative Example 2

[0076] The carbon-silicon composite material obtained in Comparative Example 1 was mixed with a sodium carboxymethyl cellulose binder at a mass ratio of 8:1 to obtain a negative electrode for a lithium battery.

[0077] The electrochemical rate performance of the upper electrode material at different current densities was tested, and the rate curve was obtained as shown in the figure Figure 6 As shown;

[0078] Figure 6 In the figure, the axial coordinate Capacity is the capacity, and the horizontal coordinate Cycle number is the number of cycles;

[0079] from Figure 6 It can be seen that in the capacity test of the lithium battery negative electrode in this embodiment at different current densities, the initial capacity is low, which is 400mAh / g, and as the current density increases and the number of cycles increases, the capacity decays significantly and cannot be restored to the initial capacity at low current density, which is only 50% of the initial capacity.

[0080] This indicates that the conductivity of the carbon shell in the carbon-silicon composite material produced in Comparative Example 1 is worse than the conductivity of the graphene shell of the graphene-copper-silicon composite material obtained in Example 1, and thus the capacity performance of the lithium battery negative electrode prepared therefrom is also worse than that of the lithium battery negative electrode prepared from the graphene-copper-silicon composite material obtained in Example 1.

[0081] Comparative Example 3

[0082] Preparation of copper-silicon composite materials:

[0083] S100: Weigh 0.2 g of silicon particle powder with an average particle size of 100 nm and 1 g of copper nanoparticle powder with a particle size of 500 nm, grind them in an agate mortar for more than 30 min, and mix them evenly to obtain a black powder;

[0084] S200: Dry the black powder in a vacuum oven at 80°C for 1 hour to remove excess moisture; place the dried black powder in a pure argon protective gas with a purity of 99.9% at a gas flow rate of 100 mL / min, and heat it at a rate of 10°C / min. Keep it at 600°C for 1 hour and then cool it naturally to obtain a red powder, thereby obtaining a copper-silicon composite material.

[0085] The copper-silicon composite material obtained above was observed by transmission electron microscopy (TEM), and the results were as follows: Figure 7 As shown;

[0086] from Figure 7 It can be seen that there are a large number of agglomerates in the copper-silicon composite material obtained above, indicating that the copper in the copper-silicon composite material without graphene coating is melted into blocks alone, and the silicon nanoparticles are agglomerated, and a synergistic composite structure cannot be formed.

[0087] Comparative Example 4

[0088] The copper-silicon composite material obtained in Comparative Example 3 was mixed with a sodium carboxymethyl cellulose binder at a mass ratio of 8:1 to obtain a lithium battery negative electrode.

[0089] The electrochemical rate performance of the upper electrode material at different current densities was tested, and the rate curve was obtained as shown in the figure Figure 8 As shown;

[0090] Figure 8 In the figure, the axial coordinate Capacity is the capacity, and the horizontal coordinate Cycle number is the number of cycles;

[0091] from Figure 8 It can be seen that in the capacity test of the lithium battery negative electrode in this embodiment at different current densities, the initial capacity is 1200mAh / g, and as the current density increases and the number of cycles increases, the capacity decays significantly and cannot be restored to the initial capacity at low current density, which is only 40% of the initial capacity;

[0092] This indicates that a large amount of agglomeration in the copper-silicon composite material prepared in Comparative Example 3 results in poor cycle performance of the material.

[0093] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a graphene-copper-silicon composite material, characterized in that: include: Grind and mix silicon powder, copper powder and polymethyl methacrylate particles to obtain black powder; The black powder is dried, and then the dried black powder is heat-treated in an inert protective gas to obtain a red powder; The red powder is placed in an acid solution and stirred for corrosion, followed by vacuum filtration and drying to obtain a yellow-white powder, which is a graphene-copper-silicon composite material.

2. A method for preparing a graphene-copper-silicon composite material according to claim 1, characterized in that: The mass ratio of the silicon powder, the copper powder and the polymethyl methacrylate particles is 0.1-0.2:1-2:1-1.

5.

3. A method for preparing a graphene-copper-silicon composite material according to claim 1, characterized in that: The grinding time is greater than 30 min.

4. The method for preparing a graphene-copper-silicon composite material according to claim 1, characterized in that: The drying temperature is 80-100°C.

5. The method for preparing a graphene-copper-silicon composite material according to claim 1, characterized in that: The heat treatment temperature is 550-650° C., and the heat treatment time is 1-2 hours.

6. The method for preparing a graphene-copper-silicon composite material according to claim 1, characterized in that: The acid solution is a 1.8-2.2 mol / L nitric acid or hydrochloric acid solution, the stirring speed is 200-300 r / min, and the stirring corrosion time is 1-2 h.

7. A method for preparing a graphene-copper-silicon composite material according to any one of claims 1 to 6, characterized in that: The drying temperature is 40-50°C.

8. A graphene-copper-silicon composite material, characterized in that: Prepared by the method described in any one of claims 1 to 7, comprising graphene, copper nanoparticles and silicon nanoparticles, wherein the graphene wraps the copper nanoparticles and the silicon nanoparticles.

9. A graphene-copper-silicon composite material for a lithium battery negative electrode material, characterized in that: The graphene-copper-silicon composite material is prepared by the method described in any one of claims 1 to 7; After the graphene-copper-silicon composite material is mixed with a binder, a lithium battery negative electrode material of the graphene-copper-silicon composite material is obtained.

10. The negative electrode material for lithium battery of a graphene-copper-silicon composite material according to claim 9, characterized in that: The binder is one of phenolic resin, urea-formaldehyde resin, asphalt, PVP, cellulose acetate, sodium carboxymethyl cellulose, and polyacrylonitrile, and the mass ratio of the binder to the graphene-copper-silicon composite material is 1:8-10.

Citation Information

Patent Citations

  • Graphene / silicon lithium ion battery cathode material and preparation method thereof

    CN101924211A

  • Preparation method of nitrogen-doped graphene-coated nano-silicon composite material

    CN110048098A